The Influence of Content Marketing, Content Quality, and Brand Image on the Purchase Intention of Skintific Products Through the Official TikTok - Rahmawati, Putri Adi; Farida, Lailatul (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2024)
This study aims to find out how the Influence of Content Marketing, Content Quality, and Brand Image on Puchase Intention in Skintific skincare products through TikTok video content. This research method uses quantitative methods. The population in this study is consumers of Skintific products. The sample criteria in this study are Gen Z and Millennials who use the TikTok application in Malang. The sampling technique used purposive sampling techniques and obtained 110 samples. The data analysis technique uses multiple linear regression analysis. The results of this study show that content marketing variables have a partial positive and significant effect on purchase intention. Content quality variables have a partially positive and significant influence on purchase intention. Brand image variables have a partially positive and significant effect on purchase intention. Then the simultaneous relationship between the variables of content marketing, content quality, and brand image has a positive and significant effect on purchase intention. This research can be used by companies in organizing sales promotions so that they are in great demand by broad consumers.